2000
DOI: 10.1074/jbc.m000439200
|View full text |Cite
|
Sign up to set email alerts
|

γ1- and γ2-Syntrophins, Two Novel Dystrophin-binding Proteins Localized in Neuronal Cells

Abstract: Dystrophin is the scaffold of a protein complex, disrupted in inherited muscular dystrophies. At the last 3 terminus of the gene, a protein domain is encoded, where syntrophins are tightly bound. These are a family of cytoplasmic peripheral membrane proteins. Three genes have been described encoding one acidic (␣1) and two basic (␤1 and ␤2) proteins of ϳ57-60 kDa. Here, we describe the characterization of two novel putative members of the syntrophin family, named ␥1-and ␥2-syntrophins. The human ␥1-syntrophin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
104
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 64 publications
4
104
0
2
Order By: Relevance
“…Aside from a-syntrophin, the ubiquitously expressed b 1 and b 2 (Ahn et al, 1996) and the brain-specific g 1 and g 2 isoforms (Piluso et al, 2000) have all been characterized. Furthermore, recent studies showed that there can be up to four distinct syntrophin binding sites within a single DGC, which can theoretically bind any combination of syntrophin (Peters et al, 1997;Newey et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Aside from a-syntrophin, the ubiquitously expressed b 1 and b 2 (Ahn et al, 1996) and the brain-specific g 1 and g 2 isoforms (Piluso et al, 2000) have all been characterized. Furthermore, recent studies showed that there can be up to four distinct syntrophin binding sites within a single DGC, which can theoretically bind any combination of syntrophin (Peters et al, 1997;Newey et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Dès 1987, date de sa découverte [1], et durant environ 2 décennies la dystrophine voyait presque chaque année autour d'elle apparaître de nouveaux partenaires aussi bien ancrés dans la membrane musculaire que distribués dans le cytoplasme environnant et formant ainsi un large complexe macromoléculaire [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. On va ainsi identifier une protéine apparentée à la dystrophine comme la dystrobrévine avec 2 versions différentes (α et β) et 7 à 8 isoformes respectivement.…”
Section: La Dystrophine Et Son Environnement Musculaireunclassified
“…Sections were incubated with 10% normal donkey serum and 0.3% Triton X-100 for 1 h to block nonspecific absorption sites and then incubated overnight at 4°C with anti-syntrophin ␥2 rabbit polyclonal antibody (diluted 1:200 in 5% normal donkey serum; a kind gift from Dr. Vincenzo Nigro). The specificity of this antibody for syntrophin ␥2 has been previously shown by Piluso et al (22). After several rinses in PBS, the sections were incubated for 1 h with donkey, anti-rabbit IgG conjugated to CY3 (1:100 dilution in 2.5% normal donkey serum), rinsed in PBS, and coverslipped in glycerol-PBS containing an anti-fade reagent.…”
Section: -Pcr Poly(a) Rna Isolation and C-dna Library Preparation-prmentioning
confidence: 99%
“…Each syntrophin is encoded by a separate gene but shares a common domain organization. Each syntrophin contains two tandem pleckstrin homology domains at the N terminus, a single PDZ domain, and a highly conserved C terminus syntrophin-unique region (22,23). The PDZ domains of syntrophins ␣, ␤1, and ␤2 but not ␥1 are known to interact with SCN5A and with SCN4A, a skeletal muscle Na ϩ channel, via the C terminus sequence motif (E(S/T)XV) (14,15,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation